2018
DOI: 10.1051/0004-6361/201732267
|View full text |Cite
|
Sign up to set email alerts
|

Three-lobed near-infrared Stokes V profiles in the quiet Sun

Abstract: Context. The 1.5-m GREGOR solar telescope can resolve structures as small as 0.4" at near-infrared (NIR) wavelengths on the Sun. At this spatial resolution the polarized solar spectrum shows complex patterns, such as large horizontal and/or vertical variations of the physical parameters in the solar photosphere. Aims. We investigate a region of the quiet solar photosphere exhibiting three-lobed Stokes V profiles in the Fe I spectral line at 15648Å. The data were acquired with the GRIS spectropolarimeter attach… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…Therefore, we have found linear polarization located between opposite polarity vertical fields in both ROI A and C, and it is certainly conceivable that this may be characteristic of how the deep photospheric magnetic field is organized at these scales and resolution. Mixed polarity Stokes V profiles have also been observed in the infrared in previous studies (Khomenko et al (2003);Martínez González et al (2016); Kiess et al (2018)). Multi-lobed Stokes V profiles have been found in highly blue-or red-shifted Stokes profiles, indicative of supersonic magnetic flows at possible sites of reconnection (Borrero et al 2013).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Therefore, we have found linear polarization located between opposite polarity vertical fields in both ROI A and C, and it is certainly conceivable that this may be characteristic of how the deep photospheric magnetic field is organized at these scales and resolution. Mixed polarity Stokes V profiles have also been observed in the infrared in previous studies (Khomenko et al (2003);Martínez González et al (2016); Kiess et al (2018)). Multi-lobed Stokes V profiles have been found in highly blue-or red-shifted Stokes profiles, indicative of supersonic magnetic flows at possible sites of reconnection (Borrero et al 2013).…”
Section: Discussionsupporting
confidence: 73%
“…However, the question remains unresolved as to whether this substructure is generated by gradients along the LOS or across the solar surface. Kiess et al (2018) inverted these data, focusing Stokes V profiles with more than two lobes, indicative of the presence of opposite polarities co-existing either vertically (along the LOS) or horizontally within the resolution element.…”
Section: Introductionmentioning
confidence: 99%
“…) and this property of the infrared lines has been exploited to probe deep into the solar photosphere, in the sunspot penumbrae, by Borrero et al Article number, page 1 of 11 arXiv:1904.07306v1 [astro-ph.SR] 15 Apr 2019 A&A proofs: manuscript no. Deep_convection_arxiv (2016), but also in the quiet Sun (Martínez González et al 2007Lagg et al 2016;Martínez González et al 2016;Kiess et al 2018). Also, the mean solar spectrum of these lines was modeled, either to infer atomic parameters (Borrero et al 2003) or to verify state-of-the-art MHD simulations (Beck et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Observing quiet-sun intergranular lanes, Kiess et al (2018) found near-ubiquituous three-lobe Stokes V signals in the 1564.8 nm Fe i line. Carrying out detailed modeling and inversions, these authors concluded that two magnetic field components with very different strengths (9 G and 1147 G) coexisting in the same pixel are required to explain the signals.…”
Section: Curling the Curl: The Nlte Source Function And The Backgrounmentioning
confidence: 95%
“…Despite this, we think that the preliminar results support our model as a good starting point for explaining the signals without assuming spatiotemporally unresolved components. Kiess et al 2018). Red profiles: NLTE synthesis obtained with our model assuming a two-level atom for the transition e 7 D 1n 7 D o 1 , with A u = 1.94 · 10 −6 , effective Landé factor g eff L = 3, negligible damping constant a = 0, T = 8000 K, and w 1 0 = −0.03.…”
Section: Curling the Curl: The Nlte Source Function And The Backgrounmentioning
confidence: 99%